An Indonesian Teacher’s Code-Switching in a Senior High School EFL Speaking Classrooms - Zahra, Putri Al (Peneliti.net, 2024)
Code-switching is a unique phenomenon in people who used bilingual or multilingual language when speaking with another person. Hoffman (1991) stated that code-switching refers to the alternating employment of two languages or linguistic types within the same utterance or during the same conversation. The research aimed to find out the teacher implementation of code-switching in EFL classrooms and discover the extent to which code-switching assists students in learning English. The research focused on the data of a teacher and students speaking about code-switching. The qualitative method was used in this research employing a case study. A teacher and three students at a high school in Kawarang participated in this research. The instrument of this research used an observation checklist and interview guidelines. To analyze the data, the researcher applied thematic analysis. The findings revealed there were three types of code-switching occurred in this research. The language switch that occurred in this research is English, Indonesian, and Sundanese. The teacher implemented code-switching in greeting or opening, introducing the topic, delivering material, and closing the lesson. Code-switching had a positive impact on a teacher and students in their learning process in EFL classrooms. From the result, the research suggested that further research can explore international schools and added one more teacher participant.